Cardiorespiratory concerns shape brain responses during automatic panic-related scene processing in patients with panic disorder - Feldker, Katharina (J Psychiatry Neurosci, 2018)
BACKGROUND: Increased automatic processing of threat-related stimuli has been proposed as a key element in panic disorder. Little is known about the neural basis of automatic processing, in particular to task-irrelevant, panic-related, ecologically valid stimuli, or about the association between brain activation and symptomatology in patients with panic disorder. METHODS: The present event-related functional MRI (fMRI) study compared brain responses to task-irrelevant, panic-related and neutral visual stimuli in medication-free patients with panic disorder and healthy controls. Panic-related and neutral scenes were presented while participants performed a spatially non-overlapping bar orientation task. Correlation analyses investigated the association between brain responses and panic-related aspects of symptomatology, measured using the Anxiety Sensitivity Index (ASI). RESULTS: We included 26 patients with panic disorder and 26 heatlhy controls in our analysis. Compared with controls, patients with panic disorder showed elevated activation in the amygdala, brainstem, thalamus, insula, anterior cingulate cortex and midcingulate cortex in response to panic-related versus neutral task-irrelevant stimuli. Furthermore, fear of cardiovascular symptoms (a subcomponent of the ASI) was associated with insula activation, whereas fear of respiratory symptoms was associated with brainstem hyperactivation in patients with panic disorder. LIMITATIONS: The additional implementation of measures of autonomic activation, such as pupil diameter, heart rate, or electrodermal activity, would have been informative during the fMRI scan as well as during the rating procedure. CONCLUSION: Results reveal a neural network involved in the processing of panic-related distractor stimuli in patients with panic disorder and suggest an automatic weighting of panic-related information depending on the magnitude of cardiovascular and respiratory symptoms. Insula and brainstem activations show function-related associations with specific components of panic symptomatology.